Outcomes of Liver Resection for Metabolic Dysfunction-Associated Fatty Liver Disease or Chronic Hepatitis B-Related HCC - Liu, Lei; Xie, Si; Teng, Yu-Xian; Deng, Zhu-Jian; Chen, Kang; Liu, Hao-Tian; Huo, Rong-Rui; Liang, Xiu-Mei; Guo, Ping-Ping; Yang, Da-Long; Ma, Liang; Xiang, Bang-De; et al. (Frontiers in Oncology, 2022)
Aims This study aims to determine differences in severity of background liver disease at hepatocellular carcinoma (HCC) diagnosis and long-term survival outcomes among patients undergoing liver resection for HCC in the background of metabolic dysfunction-associated fatty liver disease (MAFLD) compared to chronic hepatitis B (CHB) alone or concurrent CHB (CHB/MAFLD). Methods Patient demographics and comorbidities, clinicopathologic data, perioperative and long-term outcomes among patients who underwent liver resection for HCC were reviewed. Overall and recurrence-free survival were calculated with the Kaplan-Meier method, with the values compared using the log-rank test. Results From January 2014 to December 2018, 1325 patients underwent potential curative liver resection of HCC; 67 (5.0%), 176 (13.3%), and 1082 (81.7%) patients had MAFLD alone, CHB concurrent with MAFLD, and CHB alone, respectively. At HCC diagnosis, fewer MAFLD patients had cirrhosis, alpha fetoprotein concentration ≥ 400 ng/mL, tumor size ≥ 5 cm, mulinodular, microvascular invasion, receiving major hepatectomy, and receiving adjuvant transarterial chemoembolization. After a median follow-up of 47 months after liver resection, MAFLD (or MAFLD plus CHB/MAFLD) patients had significantly higher overall and recurrence-free survival than CHB patients before or after propensity score analysis (all P<0.05). Conclusion Patients with HCC in the setting of MAFLD have less-severe background liver disease at HCC diagnosis and better long-term survival after curative liver resection compared to counterparts with CHB/MAFLD or CHB.